ANALISIS KANDUNGAN FORMALIN DAN BORAKS PADA BUMBU GILING YANG DIJUAL DI PASAR AJIBARANG WETAN - mildawati, ratna; Khumaini, Eko Hidayaturrohman; Prasetyawan, Fendy; Saristiana, Yuneka (UNIVERSITAS SAM RATULANGI, 2025)
Ground spices are a key ingredient used as food additives in almost every dish, whether at home or in places that sell various types of food. The use of food additives (BTP) in food production processes needs to be closely monitored. Additives that are prohibited include formalin and borax. Formalin and borax are banned because they can cause damage to the brain, liver, and kidneys, and long-term use can result in death. This study aims to determine whether formalin and borax are present in ground spices sold at Ajibarang Wetan Market. The ground spice samples examined came from two vendors: Vendor A (garlic, galangal, ginger, candlenut, red chili, turmeric, mixed spices, and coriander) and Vendor B (shallots, garlic, turmeric, red chili, candlenut, and mixed spices). The ground spice samples sold by Vendor A and Vendor B tested negative for both formalin and borax. The method used involved color reaction tests. To detect formalin, a potassium permanganate (KMnO₄) color reaction was used, and to detect borax, turmeric paper was employed. The conclusion of this study is that the borax test results for both vendors (Vendor A and Vendor B) were negative, as there was no color change to orange or reddish-brown. The formalin test results for both vendors were also negative, as there was no change in color to clear.